Lived experiences of middle-aged adults providing primary caregiving for their aging parents - Gaza, Katrina G.; Reyes, Gillian Elizabeth V.
Filipino middle-aged adults may experience having to care for their aging parents, as they are embedded in a culture heavy on familial ties. However, literature gaps continue to exist for this life stage, particularly if such individuals live in rural areas. Hence, data were gathered from 16 middle-aged adult participants who have at least one (1) sibling and co-reside with their aging parent in Dinalupihan, Bataan, a rural municipality in the Philippines. Data was analyzed through a six-phase thematic analysis. It was found that middle-aged adults provide for their parent’s basic needs, support their emotional well-being, and provide for their needs and wants financially. Consequently, they may feel challenged due to parent-child conflicts or limitations in their own resources and health. Thus, they manage challenges through various coping mechanisms. Alternatively, they may be provided both indirect (i.e., material and social) or direct (i.e., emotional) support primarily by family members or local institutions. Additionally, their role as primary caregivers may foster emotional growth and better parent-child relationships, showing that middle-aged adults may benefit from adopting the role and that aging parents do not necessarily need constant care. Nonetheless, changes in the aging parents’ health and personality over time also prompt participants to act in response to their parents’ needs and out of respect for elders. Future professionals and policymakers may respectively apply these findings to research on middle adulthood in other contexts and implement services that promote the well-being of informal caregivers.